THE IDENTITY-ORIENTED: ANALYSING THE POWER OF #MEETOO IN INDIA’S GENDER JUSTICE SOCIAL MOVEMENT - Shafira Rahmawati Handayaningrum; Adam Fahmi Nahjaruddin Prasetya; Muhammad Indrawan Jatmika (Jurnal Analisa Sosiologi, 2025)
This study examines the #MeToo movement in India as a form of digital activism advancing gender justice. Despite legal reforms such as the Criminal Law (Amendment) Act and the POSH Act (2013), institutional protections for women remain insufficient, particularly within informal sectors. Employing a descriptive qualitative approach and drawing upon secondary data, the research utilises Melucci’s theory of new social movements and Hunt and Benford’s identity-oriented framework to analyse how the movement constructs collective identity, fosters emotional solidarity, and mobilises moral commitment. The findings reveal that #MeToo in India enabled survivors to transform personal experiences of sexual violence into a shared collective narrative, using digital platforms as both spaces of testimony and resistance. The movement exposed structural inequalities, particularly caste- and class-based exclusions, while simultaneously disrupting dominant narratives through acts of online solidarity and public accountability. However, challenges persist in ensuring intersectional inclusivity and bridging the gap between digital mobilisation and institutional change. Theoretically, this article contributes to scholarship on social movements by highlighting how digital platforms facilitate identity-based mobilisation in contexts of legal and structural deficiency. In conclusion, the study demonstrates that the Indian #MeToo movement illustrates both the emancipatory potential and the structural limits of digital feminist activism in advancing inclusive gender justice.